2001
DOI: 10.1021/ja003695c
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical (DFT) Insights into the Mechanism of Copper-Catalyzed Cyclopropanation Reactions. Implications for Enantioselective Catalysis

Abstract: The mechanism of the copper(I)-catalyzed cyclopropanation reaction has been extensively investigated for a medium-size reaction model by means of B3LYP/6-31G(d) calculations. The starting ethylene complex of the N,N'-dimethylmalonaldiimine--copper (I) catalyst undergoes a ligand exchange with methyl diazoacetate to yield a reaction intermediate, which subsequently undergoes nitrogen extrusion to generate a copper--carbene complex. The cyclopropanation step takes place through a direct carbene insertion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
0
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 188 publications
(151 citation statements)
references
References 72 publications
7
138
0
6
Order By: Relevance
“…Calculations 66 and Hammett studies 67 support the addition of a very reactive metalcarbene intermediate in the early transition state to the substrate in a concerted, yet strongly asynchronous pathway with a cationic substrate character on one alkene carbon. This is represented by transition state A, rather than in the metallacyclobutane B (Scheme 15).…”
Section: General Informationmentioning
confidence: 88%
“…Calculations 66 and Hammett studies 67 support the addition of a very reactive metalcarbene intermediate in the early transition state to the substrate in a concerted, yet strongly asynchronous pathway with a cationic substrate character on one alkene carbon. This is represented by transition state A, rather than in the metallacyclobutane B (Scheme 15).…”
Section: General Informationmentioning
confidence: 88%
“…An extensive study on the importance of the nature of the support has been recently reported, confirming the need of having a lamellar anionic support to observe such surface 55 confinement effects. 10 A simple model has been proposed to explain those results, taking into account the known cyclopropanation reaction mechanism [11][12][13][14][15][16][17][18][19][20] and the strong ionpair interaction between the key copper-carbene intermediate and the support surface, as well as the steric constraints of the 60 catalytic complex. From that model we proposed the synthesis of chiral ligands without C 2 symmetry as a method to enhance the surface-complex proximity and hence the support-complex interaction, allowing the surface to effectively shield one face of the complex.…”
Section: Consequence the Isomer Cis-(1s2r) (4s) Was Preferably Obtamentioning
confidence: 99%
“…15 With the aim of rationalizing the experimental results described above, and to have a better understanding of the geometries of the key intermediates and transition structures (TS), a theoretical study of the different reaction channels of the copper-catalyzed cyclopropanation reaction with C 1 -20 symmetric aza-pyox ligands was done. Apart from the wellknown drawbacks in modeling the cyclopropanation reaction with styrene due to the flatness of the potential energy surface, [11][12][13][14][15] our main interest in this work was to evaluate the enantioselectivity of the process; therefore, all the calculations 25 were carried out using ethylene as olefin. In addition, as in previous studies, methyl diazoacetate was used in the calculations instead of ethyl diazoacetate.…”
mentioning
confidence: 99%
“…10 Some mechanistic studies of the intermolecular copper(I)-catalyzed cyclopropanations have also been published. [12][13][14] The intramolecular cyclopropanation of diazomalonates of type A in Scheme 2 (a 1,1-disubstituted olefin) is unprecedented in the literature, although there are earlier examples of both 1,2-disubstituted and even 1,2,2-trisubstituted olefins being cyclopropanated with copper catalysts. 8 Scheme 2.…”
Section: Resultsmentioning
confidence: 99%